2005
DOI: 10.1158/0008-5472.can-05-2004
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Induces Apoptosis in Germ Line Stem Cells in the Immature Rat Testis and Amifostine Cannot Protect against This Cytotoxicity

Abstract: The underlying primary damage to the seminiferous epithelium caused by chemotherapeutic regimens at childhood is largely unknown. The present investigation was designed to identify acute cytotoxic events in the testis caused by a single dose of doxorubicin. Male rats at 6, 16, and 24 days of age were injected with doxorubicin (3 mg/kg, i.p.) or vehicle (saline) alone and 24 and 48 hours later, the germ cell types and apoptotic cells in the seminiferous epithelium were examined. As indicated by microscopy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 28 publications
6
74
0
Order By: Relevance
“…Spermatogenic cells are highly susceptible to DXR, mainly due to their high mitotic activity. Spermatocytes and spermatogonia are considered predisposed to toxic stimuli, more than other components of the testis (Quiles et al 2002, Hou et al 2005.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Spermatogenic cells are highly susceptible to DXR, mainly due to their high mitotic activity. Spermatocytes and spermatogonia are considered predisposed to toxic stimuli, more than other components of the testis (Quiles et al 2002, Hou et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…DXR has been shown to adversely affect spermatogenesis as well as the quantity and quality of sperm; it exerts its toxicity via oxidative stress pathways (Sikka 1996, Suominen et al 2003, Hou et al 2005, Ateşşahin et al 2006. Previous studies have demonstrated that the level of malondialdehyde (MDA), which derives from lipid peroxidation, rises after exposure to DXR, whereas the level of GSH declines (Quiles et al 2002, Ateşşahin et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations